Student's knowledge, attitude, subjective norms, and perception towards obesity prevention behavior - Dangga, Victorianus; Prabandari, Yayi Suryo; Huriyati, Emy (Universitas Gadjah Mada, 2022)
Purpose: Obesity is an excessive accumulation of fat due to an imbalance of nutrient intake with energy used over a long time. One of the factors that can increase the incidence of obesity is a lack of knowledge about obesity prevention. Knowledge about health affects attitudes as a long-term result of exposure to information. The generated attitude can be a positive or negative response to general objects. Behavior is formed because it arises from intentions that were previously influenced by attitudes, subjective norms, and perceptions. This study aims to determine the relationship between knowledge, attitudes, subjective norms, and perceptions of obesity prevention behavior among students in the Special Region of Yogyakarta. Methods: This research was conducted using an observational descriptive cross-sectional design among students in the Special Region of Yogyakarta. The study sample size was 384 respondents. Independent variables are knowledge, attitudes, subjective norms, and perceptions of obesity prevention. The dependent variable is the behavior of obesity prevention. All variables were measured using researchers' questionnaires. Bivariate analysis used chi-square and Mann-Whitney tests. Multivariate analysis used logistic regression. Results: Bivariate analysis of knowledge and behavior showed no relationship (p>0.05), but analysis result of attitudes, subjective norms, and perceptions with behavior of obesity prevention showed a significant relationship (p<0.05). The coefficient of determination in multivariate analysis was 0.086, indicating all variables studied in influence analysis 8.6% behavior of obesity prevention. Conclusions: There is no relationship between knowledge and behavior of obesity, but there is a significant relationship between attitude, subjective norm, and perception of behavior of obesity prevention among students in the Special Region of Yogyakarta.